Are international market demands compatible with domestic social needs? Challenges in strengthening innovation capacity in kenya's horticulture industry. (27th April 2012) - Steglich, Mirjam; Keskin, Ekin; Hall, Andy; Dijkman, Jeroen
Agrifood stakeholders across the world are under ever-increasing pressure with globalization and new market demands – together with changing quality and safety requirements. The ability to respond to new challenges and opportunities is important not just for producers, but also for industries in developing countries. This article explores the horticulture sector of Kenya in order to gain a better understanding of what has most significantly contributed to its success in terms of innovation response capacity. This article presents what is entailed in 'innovation response capacity', especially for natural resource-based industries in a developing country context. It will also provide an analytical framework that draws elements from agricultural innovation capacity and the innovation systems framework. This is provided through case study research conducted in Kenya by exploring a prominent horticultural enterprise, HomeGrown Ltd. The article concludes that an important element of success in this case was the formation of a range of linkages that enabled a systemic sector response to challenges rather than isolated actions of individual players.